Cultural Conflicts as Depicted in English Movie “ East Is East” - Dyan Dini; Alfian Alfian; Al Amin (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
This study examines how the characters in the film "East is East" deal with cultural clashes and conflicts of different backgrounds. The issue with this study is that the author uses a fictional family as the subject to investigate the cultural conflicts that underlie social inequality. Cultural tensions that arise among families and in the broader community are depicted in the film. The objectives of this study are to (1) identify the cultural problems that appear in "East is East" and (2) determine how the characters handle these difficulties. In this study, researchers employed a qualitative research methodology to pay attention to the a subject of investigation and interpretation. Researchers used a qualitative research method in this research to pays attention to the object to be researched and interpreted. In this study, researchers used Sociocultural Approach theory from Lev Vygotsky, Cultural Conflict theory from Thorsten Sellin, and DMIS (Developmental Model of Intercultural Sensitivity) theory from Milton Bennet. The source of the data in this study is a film entitled "East is East" in 1999 by writer Ayub Khan Din and director Damien O'Donnell. From the results of this study, based on the theory of Cultural Conflict by Thorsten Sellin, the researcher found 2 types of cultural conflict that occurred in the film, namely Primary and Secondary Conflict, then based on the cultural conflict, the researcher found out how the characters in the film deal with cultural conflict by using the theory by Milton Bennett's DMIS, namely 4 stages, denial, defense, minimization, and acceptance.